Methods for Comprehensive Analysis of the Economic Effectiveness of Business Activities: Special Reference to R & D Expenditure - Kim, Gang-Sok; Kim, Gwang-Ik; Rim, Gwang-Nam; Jang, Sun-Nam (Business Perspective Review, 2021)
Purpose: This paper suggests the methodology for comprehensively and dynamically evaluating the economic effectiveness of business activities in a view of scientific and technological development. Methods: Authors analyze the previous studies related to evaluating the economic effectiveness of business activities and suggest the methodology using the weight coefficients and pair-evaluation standards. Results: The findings reveal that comprehensive economic effectiveness of business activities reflects the effective use of various resources including labor, material, fixed asset, liquid materials, and R&D expenditure into the business activities in a certain period of time and it must be assessed by using the integrated indicator. Implications: The findings may contribute to the theories related to the economic effectiveness of business activities. It is also likely to improve organizational decision-making.